The foodstuffs for animals in Greece. Contribution to the valorization of some by products - ΕΥΣΤΑΘΙΟΥ Λ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author is referring to the industrilization of foodstuffs animal production in Greece and the arising problems. A table is given of foodstuff chemical analysis with the arithmetical means and the standard deviation, carried out in the Laboratory, making an effort to improve our knowledge on the composition of foodstuff rations and the valoriration of some by-products